2007
DOI: 10.4321/s0365-66912007001100009
|View full text |Cite
|
Sign up to set email alerts
|

Análisis del espesor de la capa de fibras nerviosas en niños de 6 a 9 años

Abstract: RESUMENObjetivo: Establecer una base de datos para el GDx-VCC representativa para nuestra población de entre 6 a 9 años y analizar los datos obtenidos por rango de edades. Método: Se analizó la densidad de la CFN mediante oftalmoscopía de barrido con láser (GDx) a 116 niños procedentes de un único colegio y los resultados fueron sometidos a estudio estadístico por edades y en global a fin de determinar el rango de valores considerable como la normalidad para esa población y las posibles diferencias entre ellos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…However, in their study, there was no difference in RNFL thickness measurements in normal subjects with thinner or thicker corneas. In another study, Henderson and colleagues[37] found on the GDx VCC that OHT patients with thinner corneas had a higher NFI, indicating a thinner RNFL. However, no correlation is reported between CCT and RNFL thickness in healthy adult eyes.…”
Section: Discussionmentioning
confidence: 99%
“…However, in their study, there was no difference in RNFL thickness measurements in normal subjects with thinner or thicker corneas. In another study, Henderson and colleagues[37] found on the GDx VCC that OHT patients with thinner corneas had a higher NFI, indicating a thinner RNFL. However, no correlation is reported between CCT and RNFL thickness in healthy adult eyes.…”
Section: Discussionmentioning
confidence: 99%